DEVELOPMENT OF A COURSE SCHEDULE PREPARATION APPLICATION USING GENETIC ALGORITHM - Muhandhis, Isnaini; Alven Safik Ritonga; Muhammad Shubhan (Jurnal Sistem Informasi dan Bisnis Cerdas, 2025)
Preparing course schedules is an important process in campus administration. Schedule preparation must take into account existing limitations such as class limitations, teaching hours and lecturer availability. Genetic algorithm is an optimization method that can solve scheduling problems. Genetic algorithms are quite good at managing lecture schedules because they are able to solve problems with several criteria and several objectives that are modeled in the evolutionary process. This research aims to build an application to generate lecture schedules automatically with a genetic algorithm. This application is expected to help the administrative process of preparing schedules to be faster and more efficient. The research results show that the application runs well and the genetic algorithm is able to solve scheduling problems. The best genetic algorithm parameter values are population size 30, using roulette wheel selection method, mutation probability 20% and crossover probability 20% with the result of finding a solution in the 37th generation within 118 seconds